Probiotics, prebiotics, and COVID-19 infection: A review article (2020)
The beneficial live microbes of humans and animals are termed probiotics, and the chemical compounds that improve the growth of probiotics are known as prebiotics. Paraprobiotics and postbiotics refer to dead or inactivated living cells of probiotics and healthful metabolic products that are produced by the living cells of probiotics, respectively. Although the healthful, functional, nutritional, and immune benefits of probiotics and prebiotics are scientifically well established beyond a reasonable doubt, their potential biological roles against COVID-19 infection still warrant further clinical and laboratory investigation.